2012
DOI: 10.2500/ajra.2012.26.3748
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Treatments for Aspirin Exacerbated Respiratory Disease

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
0
18
0
1
Order By: Relevance
“…7 This process can be inhibited either by blocking the receptor with an LT receptor antagonist, such as montelukast, or by preventing the formation of cysteinyl-LTs with a 5-lipooxygenase inhibitor, such as zileuton. LT antagonists (LTAs) have proven efficacious in chronic inflammatory conditions of the airways, including allergic rhinitis, asthma, and aspirinexacerbated respiratory disease (AERD), [8][9][10][11] all diseases that often coexist with CRSwNP. Several studies have shown positive effects of LTAs as a primary treatment for CRSwNP.…”
mentioning
confidence: 99%
“…7 This process can be inhibited either by blocking the receptor with an LT receptor antagonist, such as montelukast, or by preventing the formation of cysteinyl-LTs with a 5-lipooxygenase inhibitor, such as zileuton. LT antagonists (LTAs) have proven efficacious in chronic inflammatory conditions of the airways, including allergic rhinitis, asthma, and aspirinexacerbated respiratory disease (AERD), [8][9][10][11] all diseases that often coexist with CRSwNP. Several studies have shown positive effects of LTAs as a primary treatment for CRSwNP.…”
mentioning
confidence: 99%
“…У пациентов с «аспириновой триадой» (aspirin exacerbated respiratory disease) (?) применение инГКС позволяет сни-зить применение пероральных ГКС и таким образом по-высить безопасность и переносимость терапии [61]. инГКС также приобретают статус препаратов выбора при хроническом РС без полипов [39,62].…”
Section: место интраназальных глюкокортикостероидов (ингкс) в терапииunclassified
“…[2][3][4][5] It's estimated that up to 45% of individuals desensitized to aspirin will have a respiratory reaction during the process. Some of the reasons for the urgency include: she has required emergent care following aspirin exposure in the past, a post-bronchodilator forced expiratory volume in the first second (FEV1) greater than 60%, but less than 70% of the patient's best, and the presence of a serious condition, in her case the basilar apex aneurysm and cerebral arterial vasospasm.…”
Section: Graded Challengementioning
confidence: 99%
“…[2][3][4][5] Smoking has been shown to increase the chance of developing AERD. [2][3][4][5] Smoking has been shown to increase the chance of developing AERD.…”
Section: More About Aerdmentioning
confidence: 99%
See 1 more Smart Citation